Irreconcilable Differences: Conceptualizing Conflict in Industrial Relations and Organizational Behaviour - Dickey, Todd (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractOver the past several decades, industrial relations (IR) scholars have consistently advocated for better integration of their conflict theory and empirical research with that of the neighbouring discipline of organizational behaviour (OB). Achievement of such a goal has nonetheless been a continuing challenge. Offering a novel perspective on the quest for integration, this paper categorizes the distinct and dissimilar conceptual norms of conflict in IR and OB, concluding that conceptualizations of conflict in the two disciplines are built upon irreconcilable logics. Although a unified conceptualization of conflict across these differing logics is not possible, a better understanding of their irreconcilability could facilitate a more robust and ultimately fruitful dialogue among IR and OB researchers.SummaryOver the past several decades, industrial relations (IR) scholars have consistently advocated for better integration of their theory and empirical research on conflict with that of the neighbouring discipline of organizational behaviour (OB). Achievement of such a goal has nonetheless been a continuing challenge.Offering a novel perspective on the quest for integration, this paper categorizes the distinct and dissimilar conceptual norms of conflict in IR and OB. Conflict is normally spatial in IR and temporal in OB. In IR, the existence of conflict is commonly determined by the observer (i.e., the researchers). In OB, it is determined by the observed (i.e., the parties in the workplace, be they individuals, teams or organizations).This paper argues that conceptual norms of conflict in IR and OB are built upon distinct, irreconcilable logics. The norm in IR is labelled a Spatial/Observer-determined (SO) logic, while the norm in OB is labelled a Temporal/Party-determined (TP) logic. The SO logic conceptualizes conflict spatially as a situation or state of affairs that can be determined by a researcher or other observer. Conflict itself is conceptualized as existing spatially among opposing interests, objectives or values. Alternatively, the norm in OB research is to utilize a TP logic that conceptualizes conflict as a temporal process between or among opposing parties, who determine when it begins and ends. Although a unified conceptualization of conflict across these differing logics is not possible, a better understanding of their irreconcilability could facilitate a more robust and ultimately fruitful dialogue among IR and OB researchers.